Investigating Total Annual Average Daily Traffic as a Surrogate for Motorcycle Volumes in Estimating Safety Performance Functions for Motorcycle Crashes. Issue 1 (2017) - Lyon, Craig; Persaud, Bhagwant; Himes, Scott
Data on traffic volumes are required to estimate the safety performance functions (SPFs) used to develop crash modification factors and for various safety management applications. Estimation of SPFs for motorcycle crashes can be especially challenging because few jurisdictions collect motorcycle traffic volume data systematically. To address this challenge, analyses with data from Florida, Pennsylvania, and Virginia were conducted to explore how much predictive power for an SPF was lost when motorcycle traffic volumes were not known. The results of the analyses showed that when motorcycle volumes were unknown, the use of total annual average daily traffic on its own was sufficient to develop motorcycle crash SPFs. The potential bias from missing motorcycle-specific annual average daily traffic was sufficiently negligible where it existed, not to preclude SPF development. A more significant issue in the development of motorcycle crash SPFs is to work with a crash type that is relatively rare, so that SPFs cannot be developed for all motorcycle crash types or site types.